2012
DOI: 10.1073/pnas.1212019110
|View full text |Cite
|
Sign up to set email alerts
|

Structural elements in the Girk1 subunit that potentiate G protein–gated potassium channel activity

Abstract: G protein-gated inwardly rectifying K + (Girk/K IR 3) channels mediate the inhibitory effect of many neurotransmitters on excitable cells. Girk channels are tetramers consisting of various combinations of four mammalian Girk subunits (Girk1 to -4). Although Girk1 is unable to form functional homomeric channels, its presence in cardiac and neuronal channel complexes correlates with robust channel activity. This study sought to better understand the potentiating influence of Girk1, using the GABA B receptor and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
21
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 30 publications
0
21
1
Order By: Relevance
“…promote levels of GIRK2-containing channels on the cell surface comparable to wild-type GIRK1 (17). Here, we found that, whereas MPD activated GIRK-dependent responses in all transfected cells, ML297 sensitivity required the P-M2 domain of GIRK1, which contains the pore helix/K + selectivity filter and second membrane-spanning domain (Fig.…”
Section: Significancementioning
confidence: 51%
See 2 more Smart Citations
“…promote levels of GIRK2-containing channels on the cell surface comparable to wild-type GIRK1 (17). Here, we found that, whereas MPD activated GIRK-dependent responses in all transfected cells, ML297 sensitivity required the P-M2 domain of GIRK1, which contains the pore helix/K + selectivity filter and second membrane-spanning domain (Fig.…”
Section: Significancementioning
confidence: 51%
“…Importantly, whereas ML297 had negligible effects on holding current in neurons from Girk1 −/− mice, baclofen evoked reliable (albeit small) currents in these neurons ( Fig. 3 A and B), likely attributable to activation of residual GIRK1-lacking channels (17).…”
Section: Significancementioning
confidence: 93%
See 1 more Smart Citation
“…1C, for an example), takes part in several aspects of GIRK regulation. First, it regulates both basal and neurotransmitter-evoked activity of the channel Kahanovitch et al, 2014;Wydeven, Young, Mirkovic, & Wickman, 2012). In particular, a single residue within the distal CT domain (Q404) selectively influences I evoked .…”
Section: The Distal C-terminus Of Girk1mentioning
confidence: 99%
“…The composition of GIRK channels can also vary across cell types, even within a single brain region (Aguado et al, 2008;Cruz et al, 2004;Fernandez-Alacid et al, 2009). Given that GIRK channels composed of different subunits exhibit distinct functional properties ( Jelacic et al, 2000;Jelacic, Sims, & Clapham, 1999;Schoots et al, 1999;Wydeven, Young, Mirkovic, & Wickman, 2012), this diversity allows for varied GIRKmediated signaling across brain regions and cell types (for a detailed discussion of GIRK channel diversity, see Chapter 5).…”
Section: Girk Channels 21 Neuronal Girk Channelsmentioning
confidence: 97%